UPAYA PENINGKATAN HASIL BELAJAR BAHASA INDONESIA SISWA SEKOLAH DASAR MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE CIRC - Aura Triana, Kayla; Ana Latias, Malida; Nisrinawati, Dini; Aghtiar Rakhman, Patra (Universitas Negeri Medan, 2024)
Abstract: The purpose of this study was to determine efforts to improve the learning outcomes of Indonesian language elementary school students using the CIRC type cooperative learning model. The technique of collecting data and information for this research is through various written sources with the Systematic Learning Review research method. Based on the results of the search and review of information, it was found that the CIRC type cooperative learning model succeeded in improving the learning outcomes of Indonesian language elementary school students. So it is recommended that teachers, especially at the elementary school level, can apply the CIRC type cooperative learning model which has been proven to improve student learning outcomes. Keyword: learning outcomes, Indonesian language, elementary school students, CIRC model Abstract: Tujuan penelitian ini adalah untuk mengetahui upaya peningkatan hasil belajar bahasa Indonesia siswa sekolah dasar menggunakan model pembelajaan Kooperatif tipe CIRC. Teknik pengumpulan data dan informasi penelitian ini melalui berbagai sumber tertulis dengan metode penelitian Systematic Learning Review. Berdasarkan hasil pencarian dan pengkajian informasi didapatkan bahwa model pembelajaran Kooperatif tipe CIRC berhasil meningkatkan hasil belajar bahasa Indonesia siswa sekolah dasar. Sehingga disarankan agar guru khususnya pada jenjang sekolah dasar dapat menerapkan model pembelajaran Kooperatif tipe CIRC yang telah terbukti dapat meningkatkan hasil belajar siswa. Keyword: hasil belajar, Bahasa Indonesia, siswa sekolah dasar, Model CIRC